Teacher Creativity in Overcoming Limitations Of Indonesian Language Learning Media at MI Al Fitrah Semarang - Zahira Moch Yusuf Baswedan; Tuti Marlina; Syamsudin Syamsudin (MASI Mandiri Edukasi, 2026)
Limited facilities and learning media remain a significant challenge in Madrasah Ibtidaiyah, particularly in Indonesian language instruction. This study aims to describe and analyze teacher creativity in overcoming the limitations of learning media at MI Al Fitrah Meteseh. The research employs a qualitative approach with a field study design. Data were collected through in-depth interviews with Indonesian language teachers, supported by classroom observations and documentation. The data were analyzed inductively through data reduction, data display, and conclusion drawing. The results reveal that the school’s learning facilities and media remain limited and are not fully supported by the institution. However, teachers continue to implement the curriculum by demonstrating creativity, such as developing simple, low-cost learning materials and applying varied instructional methods. These efforts ensure Indonesian language learning remains effective, engaging, and understandable for students despite existing limitations.